Recent Trends in Signal and Image Processing Proceedings of ISSIP 2018 - Bhattacharyya, Siddhartha; Pal, Sankar K.; Pan, Indrajit; Das, Abhijit; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents fascinating, state-of-the-art research findings in the field of signal and image processing. It includes conference papers covering a wide range of signal processing applications involving filtering, encoding, classification, segmentation, clustering, feature extraction, denoising, watermarking, object recognition, reconstruction and fractal analysis. It addresses various types of signals, such as image, video, speech, non-speech audio, handwritten text, geometric diagram, ECG and EMG signals; MRI, PET and CT scan images; THz signals; solar wind speed signals (SWS); and photoplethysmogram (PPG) signals, and demonstrates how new paradigms of intelligent computing, like quantum computing, can be applied to process and analyze signals precisely and effectively. The book also discusses applications of hybrid methods, algorithms and image filters, which are proving to be better than the individual techniques or algorithms. .
Assessment of UWAC System Performance using FBMC Technique -- Pyramid Based Multi-scale Enhancement Method for Iris Images -- Fuzzy based Classification for Fusion of Palmprint and Iris Biometric Traits -- Employing FPGA Accelerator in Real-time Speaker Identification Systems -- Character Recognition from Handwritten Image using Convolutional Neural Networks -- Malignant Melanoma Classification using Cross Platform Dataset with Deep Learning CNN Architecture -- Simple Exponential Smoothing and its Control Parameter: A Reassessment -- Quantum Inspired BAT Optimization Algorithm for Automatic Clustering of Gray Scale Images -- Face Detection and Expression Recognition using Haar - Cascade Classifier and Fisherface Algorithm.
Keywords: Signal processing; Computer vision; Telecommunication; Computer simulation; Signal, Speech and Image Processing; Computer Vision; Communications Engineering, Networks; Computer Modelling